Effects of Wall Sit and Calf Raise Training on Futsal Shooting Performance - Mochammad Ilham Maulana; Encep Sudirjo; Dinar Dinangsit (Journal Coaching Education Sports, 2026)
Shooting ability is a fundamental skill that critically determines performance effectiveness in futsal, particularly among elementary school students. However, its development is often hindered by inadequate lower limb muscle strength and ankle stability. This study investigated the effect of wall sit and calf raises training on shooting ability enhancement in futsal extracurricular participants at SDIT Wadi Fatimah. A pre-experimental one-group pretest-posttest design was employed. Eighteen students were selected using total sampling. Data were collected through shooting tests before and after an eight-week intervention. Wall sit was implemented during the first four weeks to develop leg strength, while calf raises were introduced in the final four weeks to improve ankle stability. Descriptive analysis showed increased mean shooting scores from 7.50 at pretest to 9.78 at posttest. The paired sample t-test yielded a significance value of 0.000 (p < 0.05), confirming a statistically significant improvement. These findings empirically demonstrate that the structured combination of wall sit and calf raises training effectively enhances futsal shooting ability. It is concluded that a progressive lower limb strengthening program contributes substantially to measurable improvements in shooting accuracy and consistency among young elementary school athletes.